THE EFFECT OF SOAKING DURATION OF TUBA ROOTS (Derris elliptica) ON THE MORTALITY OF THE WHITE-BACKED PLANTHOPPER PESTS (Metcalfa pruinosa) - Faradilla, Novita Indah; Maasawet, Elsje Theodora; Rambitan, Vandalita Maria Magdalena (Jurnal Pendidikan Matematika dan IPA, 2024)
Tuba root (Derris elliptica) is a plant that contains rotenone in roots where this content functions as a poison for insects, so tuba root has the opportunity to be used as a vegetable pesticide in pest control activities. Research on tuba roots as control of white-backed planthopper pests (Metcalfa pruinosa) on green deli water guava plants (Syzygium aqueum L.) has never been carried out, therefore research was conducted which aimed to determine the effect of long soaking of tuba roots (Derris elliptica) on the death of planthopper pests white back (Metcalfa pruinosa) on green deli water guava (Syzygium aqueum L.). The type of research used was experimental research using 5 treatments, namely soaking tuba roots for 12, 24, 36 and 48 hours. The data analysis technique uses the one way ANOVA test and the BNT test at the 0.05 level. The results of the one-way ANOVA test data analysis produced a significant value of less than 0.05, so it can be concluded that the length of soaking tuba roots influences the death rate of white-backed planthopper pests. The treatment that has the most influence on the death of white-backed planthopper pests is application three times a week using tuba root soaking for 12 hours with a mortality rate of 36%.